Collaborative research on Sesbania in East and Southern Africa. Proceedings of a workshop - Kategile, J.A.; Adoutan, S.B. (International Livestock Centre for Africa, 1993)
Interest in Sesbania has probably been spurred by the awareness and emphasis being given to the incorporation of multipurpose trees in tropical agricultural systems with the potential benefits of improving water and soil conservation and soil improvement in addition to providing animal feed, fuel wood and other products. Africa is the centre of origin of a number of Sesbania sp. especially perennials and this suggests that they are adaptable. On the anticipation that indigenous Sesbania can be domesticated and incorporated into the African agricultural systems, ILCA made a germplasm collection mission in Tanzania in 1987 meeting 161 accessions. Initial screening research in Tanzania, Uganda, Kenya, ICRAF and Rwanda were reported at the Kisumu meeting and these showed that the genus is adaptable and promising. However the incoming information was patch, with this realization the planning meeting agreed on a collaborative research for Eastern and Southern Africa focusing on multilocation screening of the collections. So this workshop was held in 1991 to review the research results and plan for the future. The specific objectives were to present research results from sites, to compare data with ecozone and across the ecozones, to plan future collaborative research programme, and to develop standardized research methodologies for the agreed programme.